G protein-coupled receptors signaling, trafficking and regulation - Shukla, Arun K. (Cambridge, MA Academic Press is an imprint of Elsevier, 2016)
G-Protein-Coupled Receptors: Signaling, Trafficking, and Regulation, a new volume in the Methods in Cell Biology series continues the legacy of this premier serial with quality chapters authored by leaders in the field. This volume covers research methods in G-Protein-Coupled Receptors, and includes sections on such topics signaling, trafficking and regulation.--Provided by publisher.
Includes bibliographical references and index.
Keywords: G proteins -- Receptors; Cell receptors; Cytology -- Technique; Electronic books